A Sentinel-2-Based System to Detect and Monitor Oil Spills: Demonstration on 2024 Tobago Accident - Emilio D’Ugo; Ashish Kallikkattilkuruvila; Roberto Giuseppetti; Alejandro Carvajal; Abdou Mbacke Diouf; Matteo Tucci; Federico Aulenta; Alessandro Ursi; Patrizia Sacco; Deodato Tapete; Giovanni Laneve; Fabio Magurano (Remote Sensing)
In this paper, we analyze the serious environmental accident caused by a massive oil spill on 7 February 2024, off the island of Tobago, using two separate algorithms, namely, the established visible near-red index (VNRI) algorithm and the novel IVI visible reflectance ratio index (IVI), both applied to Sentinel-2 satellite images. These algorithms were specifically designed to monitor oil spills in inner waters. In this paper, where the IVI is presented for the first time, its effectiveness in the open sea is also showcased allowing the identification and subsequent monitoring over time of the oily masses that threaten the coral reef of the island. The analysis suggests that with sufficient cloud-free conditions, high temporal revisit multispectral optical satellites could support the timely detection and tracking of oil masses during environmental incidents near natural sanctuaries.